Pengenalan Literasi Sains Kepada Siswa Sekolah Dasar Melalui Pembelajaran Ilmu Pengetahuan Alam Yang Kontekstual Dalam Kehidupan Sehari-Hari - Fenny Rizky Amelia; Irma Ida Sihombing; Sofia Utami Siregar; May Ardiani Rajagukguk; Ahmad Nando Telaumbanua; Yashinta Beta Riama Simanjuntak (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to enhance students’ scientific literacy and interest in learning science (IPA) among elementary school students through contextual learning connected to everyday life. Scientific literacy refers to students’ ability to understand scientific concepts and apply them in real-life contexts, enabling them not only to memorize content but also to relate it to their experiences and surrounding situations. The research employed observation, interviews, and questionnaires as data collection instruments. The study subjects were 24 fifth-grade students (Class 5A) from a public elementary school. Interviews were conducted with the homeroom teacher to identify the teaching approaches used, while questionnaires were distributed to students to assess their level of understanding and interest in science learning. By linking science learning to daily life, it is expected that students will gain a more functional understanding of scientific concepts and develop a greater interest in science subjects.